Prevalence, pattern, and predictors of ever use of complementary and alternative medicine in diabetes and hypertension: A cross-sectional study - Parteek Walia; Ranjeeta Kumari; Mahendra Singh (Wolters Kluwer Medknow Publications, 2023)
Introduction: Noncommunicable diseases (NCDs) have emerged as a pandemic globally and the situation is worse for developing nations. The four major NCDs that are responsible for a major proportion of mortality across the globe are cardiovascular diseases, cancer, respiratory diseases, and diabetes. For a country with limited resources, an integrated approach toward the management of NCDs is of particular importance. Complementary and alternative medicines (CAMs) are those health-care and medical practices that are not currently an integral part of conventional medicine system. This study was undertaken to estimate the prevalence, pattern, and predictors of CAM use among patients with NCDs (diabetes, hypertension, or both). Materials and Methods: A health-facility-based cross-sectional study was conducted at different levels of government health-care facilities in Rishikesh, Uttarakhand. CAM categories included alternative medical systems, mind-body intervention, biologically based therapies, manipulative and body-based methods, and energy therapies. Additionally, jhaad phook/local healers were also included in our study. Results: The study showed that 41% of all the study participants were ever users of CAM. While most of the users were practicing more than one type of CAM, the most common type of CAM practiced was alternative medicine system (83.3%) followed by mind-body medicine (40.2%). Except religion and place of residence of the study participant, no other factor showed a significant association with ever usage of CAM. Conclusion: CAM use was popular among study participants as almost half of them were using/consuming it and alternative medicine system was the most common type of CAM practiced.